Financing Uganda's Poverty Reduction Strategy : Is Aid Causing More Pain Than Gain? - Nkusu, Mwanza (IMF Working Papers; Working Paper ;, 2004)
Uganda's market-friendly development strategy and poverty reduction agenda have attracted large financial inflows, including aid. During 2000-02, concerns about a possible aid-induced Dutch disease were heightened by widening macroeconomic imbalances and an upward trend in the real effective exchange rate (REER). This paper shows that the REER remained broadly stable during a 10-year period and nontraditional exports increased remarkably, contrary to the predictions of the Dutch disease model. Also, economic growth was strong. This good performance is attributed to sound macroeconomic policies and important structural reforms, which have allowed an increased use of available production factors.